Modelo termo hidráulico solar para colectores solares de convección natural - Juanicó, L. E. (2016)
We present the development of a thermal-hydraulic-solar model (MTHS) for design and numerical simulation of solar thermal collectors. The MTHS is a powerful tool that, not only simulates the above, but also allows to extrapolate collector behavior for different weather patterns for any day of the year, at any latitude of the country, thus allowing maximize the efficiency of the collector in each particular case. The model takes into account in its equations the characteristic parameters of a collector, such as: optical efficiency and the overall heat loss coefficient, what defined efficiency collector. The model also includes the geometrical parameters of a collector, such as length and diameter of the absorber (values that determine the pressure drop of hydrodynamic circuit), it also uses the positioning data such as azimuth angle of the absorber, and the height of tank (values of which depends heavily the buoyant force needed to establish the natural convection in the collector).